Pengembangan LKPD Tema Tanah Airku Sub Tema Kota Palembang untuk Anak Kelompok B - Gustiana Yuantini; Hasmalena Hasmalena; Syafdaningsih Syafdaningsih (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
This research aims to develop valid and practical student worksheet. Subjects in this research were B2 and B3 groups in state kindergarten of Pembina 2 Palembang. The model developed in this development was Rowntree consisting of One to one evaluation and small group evaluation. It was aimed to see the practicality and it used the Tessmer evaluation stage which consisted of self evaluation, expert review. Data collection techniques used in this research were interview, walkthrough and observation methods. According to the results of the research, it showed that the validity of the material and design obtained an average value of 3.77 in very valid categories. Student worksheet practicality test in terms of observations with a mean value of 95% in very practical category. The small group evaluation stage obtained an average score of 92% in the very practical category. Questionnaire result was 97% in valid category. From the result, it can be concluded that student worksheet theme of my homeland and sub-theme of Palembang city for group B children is valid and practical. It is also worth to use as learning student worksheet with Theme of my homeland